Recent scattering approaches to structure and dynamics of polymer nanocomposites - Kruteva, M.; Genix, A.-C.; Holderer, O.; Oberdisse, J. (Frontiers in Soft Matter, 2022)
The characterization of polymer nanocomposites on molecular length scales and timescales is a challenging task, which is also indispensable for the understanding of macroscopic material's properties. Neutron scattering is one of the techniques which are very well-suited for studying the structure and molecular motion in such soft matter systems. X-rays can also be used for the same purpose, however, with higher energy and thus a different focus on dynamics, where they are better suited for nanoparticle motion. In this mini-review, we aim at highlighting recent results in the field of polymer nanocomposites, including nanoparticle structure in various experimental systems, from model to industrial, and polymer and particle dynamics. This allows establishing the link between microscopic and macroscopic properties, in particular rheology.